Piece Linear-Aggregate Approach for Modelling and Analysis of Fuzzy Systems - Pranevicius, H.; Kraujalis, T. (Elektronika ir Elektrotechnika, 2013)
In this paper, we use a PLA model for performance and behaviour analysis of fuzzy system. This model makes connection between fuzzy logic and formalism. A case study contains an illustration how the proposed model can be fruitfully exploited to model traffic control systems based on fuzzy logic. Piece-Linear Aggregate model for traffic signal control system has been transformed into timed automaton for verification of safety, liveness, bounded- liveness and deadlock- freeness properties based on model checking. The system performance analysis was performed using Arena software package. A comparative analysis of traffic light controllers with fixed time and fuzzy logic algorithms is given. DOI: http://dx.doi.org/10.5755/j01.eee.19.1.3261